2018
DOI: 10.1177/1179556518784296
|View full text |Cite
|
Sign up to set email alerts
|

Fit “N” Cool Kids: The Effects of Character Modeling and Goal Setting on Children’s Physical Activity and Fruit and Vegetable Consumption

Abstract: Efforts to decrease the risk of overweight and obesity should focus on children’s physical activity (PA) and fruit and vegetable (FV) consumption. Within school-based interventions, there is insufficient evidence on the effectiveness of the use of character modeling and goal setting to determine changes in step counts, MVPA, and FV consumption. Study participants were 187 students in grades 4 and 5 from 2 Title 1 elementary schools in the Southwest United States. The intervention was a quasi-experimental chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Another study conducted by Ishdorj et al examined lunch consumption based on 24-hour recalls from a nationally representative sample of public schools and found that nutrition education was not associated with fruit or vegetable consumption [110]. No impact was observed in four other studies conducted in elementary schools with nutrition education that all specifically focused on fruit and vegetable consumption, with intake measured using visual estimation [85,111,112] or digital imagery [113]. Lastly, no associations were found in three other previously described multi-component studies that incorporated both nutrition education and taste tests [76][77][78].…”
Section: Nutrition Educationmentioning
confidence: 99%
“…Another study conducted by Ishdorj et al examined lunch consumption based on 24-hour recalls from a nationally representative sample of public schools and found that nutrition education was not associated with fruit or vegetable consumption [110]. No impact was observed in four other studies conducted in elementary schools with nutrition education that all specifically focused on fruit and vegetable consumption, with intake measured using visual estimation [85,111,112] or digital imagery [113]. Lastly, no associations were found in three other previously described multi-component studies that incorporated both nutrition education and taste tests [76][77][78].…”
Section: Nutrition Educationmentioning
confidence: 99%
“…Fifteen studies measured step count [23,25,47,48,50,51,53,58,59,64,66,67,70,72]. Most studies had a medium RoB (n = 10; 66.7%).…”
Section: Step Countmentioning
confidence: 99%
“…Step count: ≥8 BCTs: Eight studies measuring step count incorporated ≥8 BCTs [23,25,51,58,59,64,66,70]. Two studies had child participants (5 to 9 years), with one finding that children took 630 more steps when using a wearable than in a typical recess period (not tested statistically) [23].…”
Section: Step Countmentioning
confidence: 99%
“…Health education and physical education provide opportunities for students to acquire skills to be physically active and engage in health-promoting behaviours for a lifetime (SHAPE America, 2014). Studies have demonstrated the effectiveness of linking physical/health education to recess by integrating curricular education concepts, such as goal setting, self-monitoring, and play and team-based activities into recess activity (Huberty et al, 2014;Larson et al, 2018;Miller et al, 2018). Early articles written about the WSCC model emphasised the importance of integrating educational components with health, and thus it is important to recognise the ways in which 'core' educational subjects can be integrated, not just from health and physical education (Lewallen et al, 2015;Michael et al, 2015).…”
Section: Curricular and Programmatic Approachesmentioning
confidence: 99%
“…Thus, a practical strategy for physical education/classroom teachers or paraprofessionals could be to modify activities and curricula developed for physical education to include a focus on rules and equipment that are also available at recess, in an effort to facilitate social play and participation. In addition, physical and health educators can promote the use of autonomous goal setting and suggest recess as a discretionary time period that can be used to facilitate goal attainment (Larson et al, 2018).…”
Section: Curricular and Programmatic Approachesmentioning
confidence: 99%